THE STANDARD OF MODERN UZBEKISTAN PROBLEMS AND PROSPECTS - Akhmedov Bekhzod (PEDAGOGS, 2024)
Annotation. One of the issues discussed was the introduction of compliance with the GPP (Good Pharmacy Practice) standard in pharmacy organizations. This standard, along with increasing the role of the pharmacist in society, will change the essence of the sale of medicines and the quality of pharmaceutical services provided. The implementation and strict adherence to the standard will be a key moment in improving the healthcare system and contributing to improving the level of healthcare in the Republic of Uzbekistan. The implementation of the GPP standard for pharmacy organizations of the Republic of Uzbekistan and its impact on the quality of pharmaceutical services was also considered. The implementation of this standard will contribute to the improvement of the healthcare system and increase the level of public health. GPP testing focuses on three points: the order of taking medicines, storage conditions and pharmaceutical recommendations.